Physically Present but Spiritually Distant: The View of the European Union in Poland - Polak Aleksandra; Hartwell Christopher A.; Sidło Katarzyna W. (Comparative Southeast European Studies)
The Polish people remain staunchly in favour of the concept of a European Union. Paradoxically though, there has been strong and continued electoral support for Law and Justice (PiS), its ruling party, despite its insistence on precipitating and then continuing multifaceted conflicts with EU institutions. This article examines the internal structural changes in Poland and the attitudes to the EU of Poland’s leaders; the article will argue that those attitudes have deepened pre-existing divisions over integration. By fusing the triple modernization theory of European integration with a two-dimensional concept of party-based Euroscepticism, the article shows how PiS’s ambiguous discourse on European integration, combined with an increasingly instrumental approach to the EU by the Polish electorate—and that electorate’s deepening polarization—have secured steady support for PiS from ostensibly Europhile voters.